Теоретичні основи формування лідерських якостей учнівської молоді - Сушик, Наталія Степанівна; Sushyk, Nataliia S. (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Формування нових політичних, соціально-економічних, соціально-культурних відносин у суспільстві залежить від того, наскільки кожна особистість займає активну життєву позицію, готова до участі в демократичному управлінні суспільством, є лідером свого життя. Тому проблема формування лідерських якостей учнівської молоді є актуальною. Forming of new political, social-economic, social-cultural relations in society depends on that, as far as every personality occupies active vital position, ready to participating in a democratic management society, is the leader of the life. Therefore a problem of forming of leader qualities of student’s young people is actual. The tasks of research provide for: to define essence, functions, types, qualities of leaders; to ground a purpose, task, maintenance, terms of forming of leader qualities of student’s young people. The purposeful forming of leader qualities of student’s young people takes place in development, studies, education, intercourse, activity of personality, at creation of optimum social pedagogical terms.
Theoretical Bases of Forming of Leader Qualities of Student’s Young People
Роботу виконано на кафедрі соціальної педагогіки та педагогіки вищої школи СНУ ім. Лесі Українки
Keywords: лідер; leader; функції лідера; functions of leader; типи лідерів; types of leaders